Istiraatijiyyah Taklim al-Lughah al-'Arabiyyah bi al-Al'ab al-Lughawiyah - Akhmad Syaifuddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2019)
As we know, the teaching of the Arabic language has spread throughout Indonesia, whether in formal or non-formal institutions, and whether in schools, institutes, or universities. However, unfortunately, Arabic language teaching in our country still suffers from various problems. One of these problems is the low motivation of students in the learning process. The author found this low level of motivation among students in both schools and universities. After analyzing the situation, the author found that the problem of students’ motivation is largely concentrated in four aspects: learning drive and needs, hopes and aspirations for the future, and the learning environment. The author then concluded that most students are weak in these four aspects. Therefore, the author attempted to propose an Arabic language teaching strategy using language games, as language games play an important role in stimulating and maintaining learners’ motivation.